Congenital facial nerve palsy: Single center study - Baelen, Hermine; Esschendal, Anne-Marie; De Brucker, Yannick; Foulon, Ina; Topsakal, Vedat; Gordts, Frans (Frontiers in Pediatrics, 2023)
Objectives This study will list the most common comorbidities of congenital facial nerve palsy and how to detect and treat them, with special attention for ENT-problems such as hearing loss. Congenital facial nerve palsy is a very rare entity but in UZ Brussels hospital there was a follow-up of 16 children in the last 30 years. Methods Literature review has been done, combined with thorough research of our own series of 16 children with congenital facial nerve palsy. Results Congenital facial nerve palsy can be part of a known syndrome, most commonly Moebius syndrome, but can also appear solely. It appears often bilateral and with a severe gradation. In our series, hearing loss is frequently seen in association with congenital facial nerve palsy. Other abnormalities are dysfunction of the abducens nerve, ophthalmological problems, retro- or micrognathism and abnormalities of limbs or heart. The majority of the children in our series underwent radiological imaging (CT and/or MRI): the facial nerve but also the vestibulocochlear nerve and middle and inner ear can be evaluated. Conclusion A multidisciplinary approach of congenital facial nerve palsy is recommended as it can affect various bodily functions. Radiological imaging needs to be done to acquire additional information that can be useful for diagnostic and therapeutic purposes. Although congenital facial nerve palsy may not be treatable itself, its comorbidities can be treated and improve the quality of life of the affected child.